The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10295-007-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

Patagonian wines: the selection of an indigenous yeast starter

Abstract: The use of selected yeasts for winemaking has clear advantages over the traditional spontaneous fermentation. The aim of this study was to select an indigenous Saccharomyces cerevisiae yeast isolate in order to develop a regional North Patagonian red wine starter culture. A two-step selection protocol developed according to physiological, technological and ecological criteria based on killer interactions was used. Following this methodology, S. cerevisiae isolate MMf9 was selected among 32 indigenous yeasts pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 25 publications
3
44
0
4
Order By: Relevance
“…Table III H2S production by indigenous S. cerevisiae isolates In a study performed for the selection of indigenous S. cerevisiae isolates suitable for wine production, H 2 S production of 32 S. cerevisiae isolates were tested and it was reported that all of the tested isolates produced H 2 S (Lopes et al, 2007). Also, Spiczki et al (2001) reported that all of the tested S. cerevisiae, S. paradoxus and S. bayanus strains were found to produce H 2 S at the level of 5 and it is recommended the strains to be genetically modified before using as starter culture for wine fermentation.…”
Section: Hydrogen Sulphide Foam and Acetic Acid Productionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table III H2S production by indigenous S. cerevisiae isolates In a study performed for the selection of indigenous S. cerevisiae isolates suitable for wine production, H 2 S production of 32 S. cerevisiae isolates were tested and it was reported that all of the tested isolates produced H 2 S (Lopes et al, 2007). Also, Spiczki et al (2001) reported that all of the tested S. cerevisiae, S. paradoxus and S. bayanus strains were found to produce H 2 S at the level of 5 and it is recommended the strains to be genetically modified before using as starter culture for wine fermentation.…”
Section: Hydrogen Sulphide Foam and Acetic Acid Productionsmentioning
confidence: 99%
“…In another study, ethanol tolerance of wine yeasts was investigated and 106 of 632 yeast strains were found to grow at 10% (v/v) ethanol concentration (Benítez et al, 1983). Lopes et al (2007) reported that 32 indigenous S. cerevisiae strains were able to begin fermentation at 5 and 10% (v/v) ethanol concentration. Besides, it was reported that only three of the tested S. cerevisiae strains were able to ferment at 15% (v/v) ethanol concentration.…”
Section: Ethanol and So 2 Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Las especies de levaduras que intervienen en la fermentación del mosto de la uva, en particular la más extendida de ellas, S. cerevisiae, incluye un gran número de cepas cuyas propiedades tecnológicas son extremadamente variables [2][3][4]). Poder diferenciar a un nivel intraespecífico (cepas) las levaduras S. cerevisiae resulta fundamental en diversos aspectos de la microbiología enológica.…”
Section: Introductionunclassified